SHORTAGE OF PEDIATRIC CARDIAC SURGEONS: CAUSES AND CONSEQUENCES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The global shortage of pediatric cardiac surgeons represents a critical challenge in modern healthcare systems, with far-reaching implications for child mortality rates and the accessibility of life-saving interventions. The results indicate that the shortage stems from a convergence of prolonged training requirements, inadequate institutional investment, geographic maldistribution of specialists, and the high-complexity nature of the specialty.